2008
DOI: 10.1111/j.1365-2435.2008.01396.x
|View full text |Cite
|
Sign up to set email alerts
|

Chlorophyll fluorescence, predawn water potential and photosynthesis in precipitation pulse‐driven ecosystems – implications for ecological studies

Abstract: Summary 1.A major research focus in population and community ecology is to establish a mechanistic understanding of plant interactions and demographic responses. The first step towards this mechanistic approach relies on understanding the differences in stress caused by different environmental conditions. Leaf-level photosynthetic rate ( A ) within and among plant populations provides important insight into population and community processes, but is difficult to acquire with sufficient replication under field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 23 publications
2
34
0
1
Order By: Relevance
“…Sin embargo, la menor Kf también se correlaciona con menores tasas de conductancia estomática y de asimilación de carbono, por lo cual las plantas que ven disminuida su Kf ven reducida directamente sus tasas fotosintéticas (Nardini et al 2008, Hubbard et al 2001, Resco et al 2008, Brodribb & Field 2010. Esto podría llegar a ser una limitante en la respuesta fotosintética de estas plantas al incremento en la temperatura proyectada por el cambio climático.…”
Section: Discussionunclassified
“…Sin embargo, la menor Kf también se correlaciona con menores tasas de conductancia estomática y de asimilación de carbono, por lo cual las plantas que ven disminuida su Kf ven reducida directamente sus tasas fotosintéticas (Nardini et al 2008, Hubbard et al 2001, Resco et al 2008, Brodribb & Field 2010. Esto podría llegar a ser una limitante en la respuesta fotosintética de estas plantas al incremento en la temperatura proyectada por el cambio climático.…”
Section: Discussionunclassified
“…Fewer studies have examined how native and invasive species respond to shorter-term changes (days) in environmental factors (Durand and Goldstein 2001;Yamashita et al 2000) and many of these studies have focused on grasses (Huxman et al 2004;Ignace et al 2007;Resco et al 2008). In this study, we conducted two experiments to investigate stress and stressrecovery of native and invasive species over a seven day period.…”
Section: Introductionmentioning
confidence: 98%
“…1, 5). Resco et al (2008) also reported low predawn Fv/Fm due to lasting photoinhibition after prolonged (a 2-month) drought, which was accompanied by 75% loss of mean maximum assimilation rate for two perennial C4 grasses in the Sonoran (Manzanera & Martínez-Chacón 2007). However, a marked decline in annual shoot growth was observed for P. alba in a simultaneous study at our experimental site in 2003 compared with previous and subsequent years (Peñuelas et al 2007).…”
Section: Ecophysiological Responses To Extreme Weather In 2003 Summermentioning
confidence: 92%